2022
DOI: 10.3389/fgwh.2022.1020163
|View full text |Cite
|
Sign up to set email alerts
|

Detection and management of postpartum haemorrhage: Qualitative evidence on healthcare providers' knowledge and practices in Kenya, Nigeria, and South Africa

Abstract: BackgroundPostpartum haemorrhage (PPH) is the leading cause of maternal death globally. Most PPH deaths can be avoided with timely detection and management; however, critical challenges persist. A multi-country cluster-randomised trial (E-MOTIVE) will introduce a clinical care bundle for early detection and first-response PPH management in hospital settings. This formative qualitative study aimed to explore healthcare providers' knowledge and practices of PPH detection and management after vaginal birth, to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Lack of training of the HCPs, risk factor screening, timely diagnosis, volume administration, blood transfusion and hospital infrastructure were some barriers in PPH detection and management reported in this study. Although the WHO recommends the appointment of well trained staff to prevent and manage the PPH (31), the shortage of well-trained healthcare staff is global challenge but it is intensi ed in LMICs including Pakistan (13,20,21,31). Only one respondent of this study attended an awareness session conducted by an institution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lack of training of the HCPs, risk factor screening, timely diagnosis, volume administration, blood transfusion and hospital infrastructure were some barriers in PPH detection and management reported in this study. Although the WHO recommends the appointment of well trained staff to prevent and manage the PPH (31), the shortage of well-trained healthcare staff is global challenge but it is intensi ed in LMICs including Pakistan (13,20,21,31). Only one respondent of this study attended an awareness session conducted by an institution.…”
Section: Discussionmentioning
confidence: 99%
“…The reason could be the unfamiliarity of modern trends due to unavailability of technology, no access to research, no compulsion of updating practices by hospital management, unavailability of training and awareness sessions. These trends are very common in other LMICs (12,19,31). Even when there is a global consent about the importance of establishing management protocols for PPH, there are no universal practice guidelines (32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…found that by task shifting point‐of‐care ultrasound to health workers without prior ultrasound training, it can be implemented in a variety of low‐resource contexts with short‐term training. Akter et al 41 . provided formative qualitative data on a critical care bundle that showed that early detection and management of postpartum hemorrhage could be improved through in‐service and multidisciplinary trainings and simulations as well as through objective means of assessing blood loss.…”
Section: Discussionmentioning
confidence: 99%